The Effect of the Covid-19 Pandemic on the Price of Staple Foods in Medan City - Manihuruk, Ekamonika; Rachmadhan, Aditya Arief (Jurnal AGRISEP, 2024)
Staple food must be available in sufficient quantities and at affordable prices. However, the COVID-19 pandemic has restricted public access and disrupted food distribution. As one of the most affected cities, Medan City is facing the threat of rising food prices due to the COVID-19 pandemic. This study aims to analyze the impact of the COVID-19 pandemic on staple food prices in Medan City. The commodities that are the focus of the research are: (1) rice, (2) white sugar, (3) palm oil, (4) chicken eggs, (5) chicken meat, and (6) beef. This study used weekly time series data which is divided into two periods; the period before the COVID-19 pandemic (2018-2019) and during the COVID-19 pandemic (2020-2021). Data analysis was performed using the ANOVA method; where the price difference shows the impact of the COVID-19 pandemic on food prices. The results of the analysis show that the COVID-19 pandemic has had a significant impact on increasing staple food prices in Medan City for the commodities: (1) rice, (2) white sugar, (3) palm oil, (4) chicken eggs, and (5) beef. The results of the study also show that the COVID-19 pandemic has had a negative implications on the food security in Medan City. This research emphasize the government intervention in stabilizing staple food prices during extraordinary conditions (such as the COVID-19 pandemic) to preserve food security in urban area.